Rapid formation of a severe regional winter haze episode over a mega-city cluster on the North China Plain. (April 2017) - Li, Jie; Du, Huiyun; Wang, Zifa; Sun, Yele; Yang, Wenyi; Li, Jianjun; Tang, Xiao; Fu, Pingqing
Abstract: The Nested Air Quality Prediction Model System (NAQPMS) was used to investigate an extreme regional haze episode persisting over the Beijing-Tianjin-Hebei megacity cluster from November 26 to December 1, 2015. During this extreme haze event, the regional daily mean PM2.5 exceeded 500 μg/m3. We found that local emissions were the main source of haze over Beijing and Hebei in the early formational stage of this episode. The accumulation of regionally transported, highly aged secondary inorganic aerosols (SIA) along the foot of the mountains was responsible (60%) for the rapid increase of surface PM2.5 in Beijing between November 30 and December 1, although PM2.5 concentrations in the source regions of Hebei province were lower. The height of regional transport ranged from 200 to 700 m above ground level, with a slow increase with increasing distance of the source regions from Beijing. This indicates that more attention should be given to point sources at heights of 200–500 m in order to reduce the contribution of transport. The contribution of local emissions to haze in Beijing was mostly concentrated below 300 m above ground level, and was more significant for black carbon (BC) and organic matter (OM) than SIA. Tagging of pollutants by emission time showed that PM2.5 had been aged before it arrived at Beijing, and PM2.5 formed one or more days prior to arrival was twice that formed on the arrival day. This suggests that control measures would be more effective if they were implemented two days prior to haze episodes. In contrast to Beijing, haze in Tianjin was governed by transport from outside sources, whereas in cities located in Hebei province this episode resulted from local emissions. Graphical abstract: Highlights: Regional transport was the main cause of PM2.5 rapid increase in a regional haze event in North China. The main body of regional transport appeared in the layer of 200-700m above ground level. PM2.5 has been highly aged because their elapsed time from source to receptors reached two days. Abstract : Regional transport of highly aged PM2.5 was responsible for the rapid increase of PM2.5 during a severe haze episode in Beijing in winter 2015.